Infestasi skabies pada ternak kerbau rawa di desa Sukamaju kecamatan Ciampea kabupaten Bogor - Upik Kesumawati Hadi; Angga Puji Nugraha (ARSHI Veterinary Letters, 2019)
The parasitic disease is one of the factors that can reduce the productivity of livestock. This study was conducted to identify the scabies cases in swamp buffaloes including species of mites, the clinical symptoms, and the prevalence. The 12 of swamp buffaloes were observed by physical examinations, followed by laboratory observations, and processing the collected mites, and finally detailed identifications. The result showed that based on physical examination, there were 2 of 12 swamp buffaloes showing clinical symptoms of scabies. The species of mite infested was Sarcoptes scabiei. The clinical symptoms of sarcoptic mange in swamp buffaloes showed alopecia, hyperemia, scabs, pruritus, and thickening of the skin. The prevalence of sarcoptic mange in buffaloes at Sukamaju village, Ciampea, Bogor was 16.6%